5 simple rules to throw a long way (Coaching Track & Field Athletics)
Discus technique covered by only 5 rules? This may seem a very strange thing to say, but I actually believe that it's true. When you look at the best discus throwers in the world, while they all have their own style all have certain technical fundamentals they adhere to. So what are these simple rules? Let's start from the back. Rule 1 - Move your weight to the left at the back of the circle Rule 2 - The right foot leads the throw Rule 3 - The right foot constantly turns in the middle Rule 4 - Land in a balanced power position Rule 5 - A complete left side block